Perceived Working Conditions and Sickness Absence - A Four-year Follow-up in the Food Industry - Anna E. Siukola; Pekka J. Virtanen; Tiina H. Luukkaala; Clas-Håkan Nygård (Elsevier, 2011)
Objectives: To analyze the association between changes in perceived physical and psychosocial working conditions and change of sickness absence days in younger and older (< 50 and ≥ 50 years) food industry employees. Methods: This was a follow up study of 679 employees, who completed working conditions survey questionnaires in 2005 and 2009 and for whom the requisite sickness absence data were available for the years 2004 and 2008. Results: Sickness absence increased and working conditions improved during follow-up. However, the change of increased sickness absence days were associated with the change of increased poor working postures and the change of deteriorated team spirit and reactivity (especially among < 50 years). No other changes in working conditions were associated with the changes in sickness absence. Conclusion: Sickness absence is affected by many factors other than working conditions. Nevertheless, according to this study improving team spirit and reactivity and preventing poor working postures are important in decreasing sickness absence.